Influence of apitoxin and melittin from Apis mellifera bee on Staphylococcus aureus strains - Marques Pereira, Ana Flavia [UNESP]; Albano, Mariana [UNESP]; Bergamo Alves, Fernanda Cristina [UNESP]; Murbach Teles Andrade, Bruna Fernanda [UNESP]; Furlanetto, Alessandra [UNESP]; Mores Rall, Vera Lucia [UNESP]; Santos, Lucilene Delazari dos [UNESP]; Orsi, Ricardo de Oliveira [UNESP]; Fernandes Junior, Ary [UNESP] (Elsevier B.V., 2020)
The antibacterial activities of apitoxin, a venom produced by Apis mellifera bee, and melittin, an antimicrobial peptide from apitoxin, were tested against planktonic and biofilm states of Staphylococcus aureus methicillin-resistant (MRSA), including clinical, and enterotoxin-producing isolates. Also, the synergism of apitoxin and melittin in combination with oxacillin were evaluated as well. The induced morphological changes on S. aureus cells of both products were detected by transmission electronic microscopy (TEM). The minimum inhibitory concentration (MIC) values were 7.2 mu g/mL, and 6.7 mu g/mL, for apitoxin and melittin, respectively. The minimum bactericidal concentration (MBC) values were 28.7 mu g/mL, and 26 mu g/mL for apitoxin and melittin, respectively. The time-kill curve assays of apitoxin or melittin with oxacillin exhibited bactericidal synergism against MRSA isolates. TEM images showed cell distortion, cell disintegration with leakage of cytoplasmic content and loss of cytoplasm content. However, apitoxin and melittin did not interfere with staphylococcal enterotoxin production or release. Thus, apitoxin and melittin are potential agents against MRSA that can serve as possible models for new antibacterial drugs.
Keywords: antibacterial activity; Bee venom; Antimicrobial peptides; Methicillin-resistant Staphylococcus aureus; MRSA; Enterotoxin-producing S. aureus